Motorcycle as a Fidusia Guarantee Object in Financing Companies in PT Adira Cabang Denpasar - Anak Agung Ayu Sri Wulan Jayanti (Warmadewa Press, 2018)
In Practice Financial Institutions and Financing Institutions operationally require another type of service, namely a guarantee facility. The guarantee itself in economy is divided into two broad lines that differentiate it, namely moving assets guarantee and immovable assets guarantee. The guarantee of immovable assets or land with all the objects attached to it is called mortgage, while for the guarantee of moving assets is regulated in Fiduciary Institutions. In Indonesia Fiduciary Institution already has its legal basis that is Law No.42 Year 1999 on Fiduciary. This research method combines between quantitative and qualitative research method to be used together in a research activity, so that it is obtained data that more comprehensive, valid, reliable and objective. Accordingly, this study will examine what is the rationale of making motorcycle as fiduciary and its implementation in the field. The regulation of Fiduciary Institution in the financing company is strictly regulated in the Laws number 42 Year 1999 on Fiduciary, is the transfer of property rights to the goods as a guarantee on the basis of trust, while the object itself remains in the hands of the owner. The implementation of imposition of motorcycle as a fiduciary at a financing company in PT.Adira Denpasar is an absolute requirement for the purpose of legal certainty that is expressly regulated in the credit agreement. This is because fiduciary security is very important for financing companies to counter the risks that may arise in the future as a result of lending by the company to the customer. Due to credit law without fiduciary in case of default at PT. Adira Denpasar, that credit without fiduciary carries a greater risk so that the legal consequences is apply that all existing and future moveable and immovable customer’s property become guarantee to debt payments. At PT. Adira Denpasar, applying prudential principles in every lending to customers by seeking guarantee or known as credit with guarantee, as one effort to minimize the risk of loss that will be suffered as a result the debtor cannot pay off the credit as agreed in the credit agreement.